Hepatocellular Carcinoma: A Comprehensive Review of Pathophysiology, Risk Factors, Diagnosis and Treatment Strategies - Dafe, Vedika N.; Hatwar , Pooja R.; Bakal , Ravindra L.; Bindod, Harshdeep V. (Journal of Drug Delivery and Therapeutics, 2025)
Hepatocellular carcinoma (HCC) is a major cause of death in cirrhosis and the fourth most common cause of cancer-related mortality globally. Chronic liver diseases, such as cirrhosis and viral hepatitis, significantly increase the risk of HCC. Early detection and treatment are vital to improving patient outcomes. HCC development involves complex interactions between liver cells, genetic changes, and environmental factors. Diagnostic approaches include imaging tests, biomarkers, and liquid biopsy. Current treatments comprise surgery, liver transplantation, radiation therapy, and systemic therapies. Preventing HCC through lifestyle changes, such as reducing alcohol intake and maintaining a healthy weight, is crucial. Understanding HCC's molecular mechanisms is essential for developing effective treatments and improving patient outcomes.Keywords: Hepatocellular carcinoma, Cancer diagnosis, Cirrhosis, chronic liver disease